2016
DOI: 10.1016/j.neuroscience.2015.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Association of myelin peptide with vitamin D prevents autoimmune encephalomyelitis development

Abstract: Multiple sclerosis is a chronic, inflammatory and demyelinating disease of the central nervous system (CNS). As there is no cure for this disease, new therapeutic strategies and prophylactic measures are necessary. We recently described the therapeutic activity of the association between myelin oligodendrocyte glycoprotein peptide (MOG) and active vitamin D3 (VitD) against experimental autoimmune encephalomyelitis (EAE). The objective of this work was to evaluate the prophylactic potential of this association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Interestingly, the stabilization of this barrier coincided with a clear accumulation of MOG-reactive cells at the draining lymph nodes, which was detected by the increased production of proinflammatory cytokines by these cells in the presence of MOG. This finding is in contrast with the downmodulatory effect of vitamin D in cytokine production by spleen cells from normal mice (Mimura et al, 2016;Missio et al, 2018). A possible explanation for these findings is that vitamin D effects are distinct in normal and EAE conditions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, the stabilization of this barrier coincided with a clear accumulation of MOG-reactive cells at the draining lymph nodes, which was detected by the increased production of proinflammatory cytokines by these cells in the presence of MOG. This finding is in contrast with the downmodulatory effect of vitamin D in cytokine production by spleen cells from normal mice (Mimura et al, 2016;Missio et al, 2018). A possible explanation for these findings is that vitamin D effects are distinct in normal and EAE conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Previous findings from our group indicated that 1,25dihydroxyvitamin D3 (1,25-VitD3) has a protective effect when given alone or in combination with the specific autoantigen (myelin oligodendrocyte glycoprotein-MOG) (Chiuso-Minicucci et al, 2015;Mimura et al, 2016). Nonetheless, relevant information concerning the local immunopathogenic changes controlled by an early vitamin D administration remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination with MOG associated with VitD, before EAE induction in C57BL/6 female mice, determined a significant clinical improvement characterized by absence of clinical score and no body weight loss. An impressive reduction in CNS inflammation, DC maturation and also cytokine production by CNS and spleen cell cultures was detected in these vaccinated animals [132]. As described in Section 6 of this chapter, this combination of MOG with VitD was also very efficient as a therapeutic procedure in the EAE model.…”
Section: Prophylactic Effect Of Vitd On Eaementioning
confidence: 65%
“…Mononuclear cells infiltrated in the CNS were obtained as previously described by Mimura et al, 2016 [38]. Briefly, sedated (ketamine/xylazine) mice were perfused with saline solution and then brain and the whole spinal cord were collected, macerated, resuspended in RPMI medium (Sigma Aldrich) supplemented with 2.5% collagenase D (Roche Applied Science) and incubated at 37°C, 5% CO 2 incubator for 45 min.…”
Section: Methodsmentioning
confidence: 99%